2000
DOI: 10.1061/(asce)0733-9429(2000)126:6(399)
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Bottom Stress in Tidal Boundary Layer from Acoustic Doppler Velocimeter Data

Abstract: Bed stresses in the bottom boundary layer of the York River estuary, Va., were estimated from 3D near-bottom velocities measured by Acoustic Doppler Velocimeters (ADVs) and also by a profiling array of electromagnetic current meters. By assuming the measurements were made in a constant stress layer, four methods of stress estimation were evaluated using ADVs: (1) direct covariance (COV) measurement; (2) turbulent kinetic energy; (3) inertial dissipation utilizing the Kolmogorov spectrum; and (4) log profile. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
302
1
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(323 citation statements)
references
References 24 publications
14
302
1
6
Order By: Relevance
“…When turbulence measurements are available, local mean shear velocity can be determined from the measured Reynolds stress distribution in the constant stress layer where stress within the water column only varies slightly from bottom stress t (Kim et al, 2000). It can be expressed as:…”
Section: Reynolds Stress Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When turbulence measurements are available, local mean shear velocity can be determined from the measured Reynolds stress distribution in the constant stress layer where stress within the water column only varies slightly from bottom stress t (Kim et al, 2000). It can be expressed as:…”
Section: Reynolds Stress Methodsmentioning
confidence: 99%
“…This approach is often taken in oceanographic studies (Stapleton and Huntley, 1995). Kim et al (2000) used the same methods as Rowinski et al (2005) and the spectral method in an estuary over a soft mud bottom and recommend further investigating the TKE method based on velocity measurements carried out at two levels. Biron et al (2004) performed laboratory experiments over fine sand, using the same methods and observed that the logarithmic profile methods gave shear velocity estimates that were significantly larger than the remaining methods.…”
Section: Introductionmentioning
confidence: 99%
“…An essential part of the field measurement was the determination of the local bed shear stress values. As Kim et al [23] reported in their study, several methods exist to estimate the bed shear stress as a function of the flow conditions. Here, the bed shear stress was estimated based on the turbulent wall law [24] using the time averaged vertical velocity profiles obtained from the fixed boat ADCP measurements and spatio-temporal averaged velocity profiles from the moving boat measurements.…”
Section: Morphological Investigation Based On Flowmeasurementsmentioning
confidence: 99%
“…15) leading to (18) or from the mean velocity (Eq. 14), which leads to (19) Yet another assumption that applies for the log-layer is the balance between the production rate of turbulent kinetic energy from shear stress (P) and the rate of energy dissipation (ε) by viscous shear (Kim et al 2000;Tennekes and Lumley 1972): (20) Assuming the energy balance, we estimate D T from ε by combining Eqs. 15, 16, 17, and 20:…”
Section: Holtappels and Lorke Turbulent Diffusion In The Bblmentioning
confidence: 99%